RETRACTED: Assessing Multidimensional Energy Poverty and Its Economic Impact on N11 Countries: Mediating Role of Energy Efficiency - Hieu, Vu Minh; Hien Phan, Thi Thu; Trung, Lam Minh (Frontiers in Energy Research, 2022)
This study seeks to estimate energy poverty using a multi-dimensional and a wide- ranging category of indicators via the combination of the GRA-SRA Approach. The study entails case study analysis of the N-11 nations utilizing data for the period 2000-2017.Thus, a formulation of multidimensional energy poverty indexes of multidimensional indicators crosswise three dimensions. Energy availability, energy affordability plus energy cleanability, pertaining to the N11 nations. The findings reveal that the total energy poverty has progressed. We discover that Bangladesh (0.65) and Pakistan (0.47) are at risk concerning energy poverty whereas the Philippines (0.36), Indonesia (0.33), and Vietnam (0.28) are less exposed to energy poverty. The comparative changes in energy poverty are discovered between the N11 nations where South Korea witnessed a consistent advancement in energy poverty whereas Iran depicted a reduced trajectory along a vacillating trend. The findings indicate that the energy sources utilized for warming homes, are important within the scenario of energy poverty as well as inequality. Contrary to traditional steps, we assess the multidimensional energy poverty at the national level instead of depths of gravity of energy poverty specifically for the energy poor as against the whole population.